Design, resistance and the performance of identity on TikTok. (April 2022) - Darvin, Ron
Abstract: One of the most downloaded apps in the world, TikTok is known widely for its act-out memes and lip-sync videos, where music and sound clips are remixed among users. While most social media platforms serve as sites of self-presentation and identity management, embedded in TikTok's design is a memetic logic that encourages imitation and replication and downplays individual identities and social connections. By conducting a multimodal discourse analysis of videos produced by popular Hong Kong-based TikTokers, this paper demonstrates how these content creators were able to resist this memetic logic by finding ways to assert their Hongkonger identities and to forge a sense of community among fellow Hongkongers. Through the production of sound memes that use sound as an anchoring mode for producing derivative videos, these TikTokers foregrounded not only their embodied selves but also local spaces and languages. By formulating and promoting context-bound tracks that connected local users, they evoked a sense of pride and affinity among Hongkongers. As content creators produce videos on TikTok, the interplay of platform affordances and constraints can be understood as a negotiation of designs: the platform design which indexes the sociotechnical purposes of app developers and software engineers and the user design which involves the assembly of semiotic resources that enable users to achieve their own intentions. Recognizing the capacity of social media platforms to program sociality, this paper asserts the need for research methods that examine the tension between the structuring power of these platforms and the agentive participation of users.